Diagnostic challenge of follicular thyroid carcinoma with insular component mixed with follicular patterned papillary carcinoma - Dr. Shaymaa Ahmed Sadek; Dr. Nazima Haider; Dr. Sohaila Fatima (Tropical Journal of Pathology and Microbiology, 2018)
Thyroid tumours with mixed follicular histological components present a great challenge for pathologists. Poorly differentiated carcinoma (or insular carcinoma) is intermediate tumour between well differentiated and anaplastic carcinomas of thyroid which may be associated with papillary and follicular thyroid carcinoma. It is important to differentiate the insular component and medullary carcinoma. We present an uncommon case of mixed follicular thyroid carcinoma with an insular component and follicular papillary variant in a 30 year old female which cannot be accurately diagnosed without application of immunohistochemistry.